A Fully Polynomial Approximation Scheme for Scheduling a Single Machine to Minimize Total Weighted Late Work - Kovalyov, M. Y; Potts, C. N; van Wassenhove, L. N (Mathematics of operations research, 1994)
This paper studies approximation algorithms for the problem of nonpreemptively scheduling n jobs on a single machine to minimize total weighted late work, where the late work for a job is the amount of processing of this job that is performed after its due date. A family of approximation algorithms DP is derived. For any > 0, DP delivers a schedule having total weighted late work which does not exceed (1 + ) times that of an optimal schedule. Since DP requires O ( n 3 log n + n 3 / ) time, the family DP is a fully polynomial approximation scheme.